The women of yesterday, today and tomorrow - Avery, Melvia Fairetta (My University, 1899)
Introduction: It is the aim of this production to treat of the past, present and future of “Earth’s noblest thing, -a woman perfected,” or, in other words, of the women of yesterday, today and tomorrow, a careful study of the subject makes us exclaim with the poet; - “Oh what makes woman lovely” virtue faith, And gentleness in suffering, - an endurance Thru scorn or trial, - these call beauty forth, Give it the stamp celestial, and admit it To sisterhood with angels.” We shall find with Washington Irving, that, “there is in every true woman’s heart a spark of heavenly fire, which beams and blazes in the dark hours of adversity.” According to the writers on primitive institutions, the position of married women was that of slavery or akin to it.
Citation: Avery, Melvia Fairetta. The women of yesterday, today and tomorrow. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Primitive Woman; Women of Present Time; The ideal Woman; Theses; Manuscripts (documents)